Obstructive Sport Apnea (OSA) and contact sports: A systematic review and meta-analysis - Howarth, N. E.; White, A. J.; Pearce, A. J.; Nowinski, C.; Cantu, R.; Ji, C.; Miller, M. A. (Sleep Epidemiology, 2022)
Obstructive sleep apnea (OSA), a frequently under-diagnosed sleep disorder, may lead to future poor health, performance, and wellbeing. Increased OSA prevalence has been reported in individuals who have had a head injury.